Techno-economic evaluation of a solar PV integrated refrigeration system for a cold storage facility. (April 2021) - Ikram, Hamid; Javed, Adeel; Mehmood, Mariam; Shah, Musannif; Ali, Majid; Waqas, Adeel
Highlights: Cold storages are important for maintaining fresh fruit quality. Suboptimal component matching can exist in conventional refrigeration systems. Solar field sizing and performance optimization of PV hybrid VCRS is accomplished. Solar PV integrated refrigeration system reduces yearly operational costs. Abstract: This paper presents a conceptual study of a solar PV integrated refrigeration system for a cold storage facility based on the conventional vapor compression system for banana fruit. In the first stage, the conventional system has been thoroughly analyzed. Mathematical modelling has shown that the condenser is oversized, while the evaporator was undersized. Furthermore, the air-conditioning compressor was also found to be oversized by approximately 12 kW after an evaluation at no-load and full-load conditions. In the second stage, the optimized system with reduced consumption was integrated to a solar PV field. The solar field sizing, and performance optimization of the proposed PV hybrid refrigeration system was accomplished in PV*SOL tool. The simulations demonstrated that with a 170 m 2 solar field, an optimized PV hybrid refrigeration system can achieve 58.1% solar fraction at a performance ratio of 59.2%, under given climatic conditions. With net metering, the hybrid system shows a high economic feasibility with the payback period of 5.2 years. The comprehensive methodology and all-inclusive results are valuable to generate explicit recommendations for repowering along with renewable integration of cold storage facilities operating in the region.